Factors Influencing Serum Concentrations of Immunoglobulin D in the Adult Population: An Observational Study in Spain. (April 2017) - Carballo, I.; Rabuñal, N.; Alvela, L.; Pérez, L.‐F.; Vidal, C.; Alonso, M.; Sopeña, B.; Gude, F.; Gonzalez‐Quintela, A.
Abstract: Immunoglobulin D (IgD) is the least studied of immunoglobulin classes. This study sought to investigate the potential relationship between demographic, metabolic, lifestyle and immunological factors, and serum IgD concentrations in a general adult population. We measured serum IgD concentrations by means of a commercial turbidimetric assay in 413 individuals (median age, 55 years; 45% males), randomly selected from the adult population of a Spanish municipality. Serum IgD concentrations displayed considerable variation in the population, ranging from undetectable (<6.7 mg/l) to 878 mg/l. Serum IgD concentrations were undetectable in 78 cases (18.9%) and >100 mg/l in 39 cases (9.4%). Median IgD was 21.9 mg/l. Serum IgD concentrations were negatively associated with age and positively associated with smoking, after adjustment for potential confounders. Overweight individuals showed lower concentrations of IgD than did normal‐weight individuals. Atopy (positivity of skin tests to aeroallergens) was not significantly associated with IgD concentrations, although non‐symptomatic atopics showed higher IgD concentrations. No consistent association was observed between serum IgD concentrations and gender, metabolic syndrome, or alcohol consumption. No significant association was found between baseline IgD concentrations and development of either allergic or immune disease after a median 11.4 years of follow‐up. In conclusion, serum IgD concentrations in adults show a wide variation in the population and may be influenced by common factors, particularly age and smoking habit. These factors should be taken into account when defining reference ranges for serum IgD concentrations.